2015
DOI: 10.1016/j.atherosclerosis.2015.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Upper versus lower limb exercise training in patients with intermittent claudication: A systematic review

Abstract: Lower extremity (LE) exercise training has been shown to contribute to improvements in Maximum Walking Distance (MWD), Claudication Distance (CD), peak oxygen uptake (VO 2peak ) and Quality of Life (QoL) in patients with intermittent claudication (IC). However, little is known regarding the efficacy of upper extremity (UE) exercise training in comparison to the widely used LE training. The objective of this systematic literature review is to identify and synthesize the available literature on the effects of UE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…Similarly, skin alterations may also be noted in vascular or neurogenic claudication [ 17 ]. Vascular intermittent claudication is a consequence of inadequate delivery of oxygenated blood flow to the peripheral tissues [ 18 ]. It is a frequent cause of leg pain and discomfort [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, skin alterations may also be noted in vascular or neurogenic claudication [ 17 ]. Vascular intermittent claudication is a consequence of inadequate delivery of oxygenated blood flow to the peripheral tissues [ 18 ]. It is a frequent cause of leg pain and discomfort [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…Vascular intermittent claudication is a consequence of inadequate delivery of oxygenated blood flow to the peripheral tissues [ 18 ]. It is a frequent cause of leg pain and discomfort [ 18 ]. In contrast to RLS, intermittent claudication occurs during activity, is relieved by rest, and lacks the urge to move [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…A review of six recent RCTs demonstrated that vigorous upper extremity exercise (arm cranking for 40-70 minutes two to three times per week for 6-24 weeks) results in improvements in mean lower leg peak oxygen consumption, walking distance, claudication distance, and quality-of-life metrics when compared to lower extremity exercise. 50 Given these findings, upper extremity and body exercise may be an alternative method of exercising CLI patients.…”
Section: Optimizing the Wound Healing Environment Through Medical Manmentioning
confidence: 99%
“…10,11 Therefore, non-painful modes of exercise, such as arm cranking, have emerged as a promising approach for patients with PAD. 12,13 Previous studies have reported that arm crank exercise significantly increased walking capacity and quality of life, 14 which may improve functional capacity in patients with PAD. However, the emotions experienced during this mode of exercise, which may influence exercise adherence and ultimately reduce cardiovascular risk, have not been examined previously.…”
Section: Introductionmentioning
confidence: 99%